Scientific Reasoning in Elementary School Children: Assessment of the Inquiry Cycle. Issue 2 (May 2019) - Schiefer, Julia; Golle, Jessika; Tibus, Maike; Oschatz, Kerstin
Scientific reasoning abilities are already developing in elementary-school-aged children and enable them to understand the world around them. The goal of the current study was to develop a new instrument for 8- to 10-year-old children in Grades 3 and 4 to measure their understanding of the steps of the scientific inquiry cycle (SIC). Such an understanding is essential for scientific reasoning as well as for inquiry-based learning approaches and, above all, for scientific practice. We developed and applied 15 items in a sample of 878 third- and fourth-grade students ( n = 434, Grade 3; n = 435, Grade 4). As confirmed by item response theory (IRT) modeling, the items produced reliable scale scores. Furthermore, we explored the relations between children's SIC performances, cognitive abilities, and epistemic beliefs. As expected, intelligence, text comprehension, experimentation strategies, and sophisticated epistemic beliefs were positively associated with children's SIC performance, a finding that helps to establish initial evidence for the construct validity of the SIC test scores.